Slope instabilities and evolution of tectonic geomorphology along the strike of the Main Boundary Thrust zone in the western Himalaya, India - Anirudh Datta; Khayingshing Luirei; Manish Mehta (Natural Hazards Research, 2024)
The Main Boundary Thrust (MBT) and Main Boundary Fault (MBF) zones of the southeast Himachal Himalaya are susceptible to various types of mass movement. Several active and in-active landslides are observed along the strike of the MBT. The landslides are mainly controlled by the brecciated and highly fractured nature of the bedrocks, and the intersecting joint sets form wedges. The movements are taking place along the fault planes, fracture planes, and bedding planes; and the types of failure are wedge failure, planar failure, toppling, rock falls, and complex landslides. The various morphotectonic features observed in the study area include fault traces, fault scarps, strath terraces, paleochannels and structurally controlled channels. Fault traces and their associated deformed landforms are the most spectacular tectonic landforms in the area. Along the strike length of the fault traces several linearly arranged sag ponds have formed, in the western segment the fault trace is observed along the MBF and the fault scarp dips south, with a maximum height of about 34 ​m. In the eastern segment the fault trace cut across the MBT, the fault trace is also displaced by transverse faults. Paleochannels and multiple levels of strath and fill terraces collectively indicate the river channel's disequilibrium state concerning the ongoing tectonic activity. The cross-cutting relation and displacement pattern of fault traces indicate later phases of tectonic activity.